Applying the Values of Local Wisdom of Samudra Kerthi in Animated Films as a Learning Medium for Early Childhood: A Case Study in Bali - I Nyoman Agus Suarya Putra; Ni Wayan Wardani; I Made Kohe Taruna Dwiputra; Putu Satria Udyana Putra (Institut Bisnis dan Teknologi Indonesia, 2025)
This study aims to develop a 2D animated learning medium for Early Childhood Education (ECE) that integrates the Balinese local wisdom of Samudra Kerthi as a strategic effort to instill environmental awareness from an early age. The urgency of this research is driven by the escalating waste crisis in Bali, particularly its impact on coastal and marine ecosystems, which necessitates educational strategies capable of fostering pro-environmental behavior in children. The development process follows the ACIA framework (Analyze, Creation, Improvement, Artwork). The Analyze phase involves identifying the requirements for effective media to stimulate environmental stewardship. The Creation phase encompasses designing animations tailored to aesthetic principles, developmental psychology, and the learning characteristics of young children. The Improvement phase was conducted through expert validation, practitioner feedback, and small-group trials to ensure conceptual clarity and audiovisual appropriateness. Findings from structured observations and teacher interviews indicate that 88% of the children comprehended the moral message and exhibited a high level of engagement with the animation. While the scope of this study remains limited to small-group trials with a brief observation period, media experts have confirmed that the animated product adheres to both pedagogical and aesthetic standards for ECE. These results suggest that local wisdom-based animation holds significant potential as an alternative medium for introducing environmental stewardship in early childhood.